The Relationship between Openness and Economic Growth: Libyan Case. - الحوتة أحمد (Dirasat in Economics and Business, 2013)
This paper estimated the relationship between openness and economic growth in Libyan economy during (1970-2005) using Autoregressive distributed lag (ARDL) approach to cointegration analysis. The empirical results show that there a unique cointegrated long run relationship among Economic Growth, openness Government Investment and population. The study provides evidence of stable negative and insignificant relationship between economic growth and openness. The paper also finds positive and significant linkage between government investment, population and economic growth. The error-correction term in the model is found to be statistically significant, confirming the validity of the long run equilibrium relationship. The coefficient estimate of the error correction term is 0.36 indicating a high speed of adjustment to equilibrium.